Sensory Integration Training and Social Sports Games Integrated Intervention for the Occupational Therapy of Children with Autism - Zhen Wang; Yulong Gui; Wenwei Nie (Hindawi-Wiley, 2022)
This paper presents a research design for an integrated intervention using sensory integration training fused with social sports games for the treatment of children with autism. This study used a multiple baseline cross-subject design in a single-subject experiment, with structured play as the independent variable and expressive language skills of children with autism spectrum disorders as the dependent variable, with three phases of intervention: baseline, intervention period, and maintenance period. The expressive language ability was examined in terms of both oral expression and gestural expression, where the intervention effect of the oral expression was analyzed in terms of four components: the total number of words, the total number of sentences, average sentence length, and vocabulary complexity of oral expression, and the intervention effect of the gestural expression was analyzed in terms of changes in the frequency of children's gestural expression behaviors. For the categories classified by sensory integration ability, there are corresponding specific training programs that combine various physical exercises and play equipment to train the various abnormal functions of children with autism. Stereotyped behavior is a repetitive, self-imposed, and purposeless physical action, usually in the form of continuous and repetitive movements, sounds, and so on. 4 times a week, 25 minutes each time, the activity of recognizing pictures and familiar objects is carried out first, and then the children choose the structured game model and the initiative to build and take turns with the researchers to build. Stereotypic behaviors cause a great deal of distress in the lives of children with autism, and it is necessary to explore how to implement positive and effective interventions. Subjects' play abilities developed after receiving effective critical response training. The subjects' practice and symbolic play showed good immediate and maintenance intervention effectiveness; their associative and functional play showed no significant intervention effectiveness. The enhancement of the sensory integration skills of children with autism through sensory integration training resulted in a relative reduction of stereotypic behavior about the stimulus-seeking function, which had a positive effect on the intervention of stereotypic behavior.